GAMBARAN DUKUNGAN SOSIAL PADA SISWA SISWI TERHADAP SIKAP MEROKOK DI SEKOLAH MENENGAH PERTAMA NEGERI KOTA PEKANBARU - Gumanty, Harima; Afandi, Dedi; ", Zulharman (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
AbstractAttitude of smoking among adolescents is still a problem that is serious enough ,the number of which increased from year to year, starting from a relatively young age so that Junior High School. Teens takes a special kind of social support from family (parents), the school environment and peers who can make them believe that they are able to resist bad influences and have a positive attitude, especially for adolescents health. Purpose of this research to gain an overview of social support on the attitudes of student toward smoking in junior high school Pekanbaru. This research is a descriptive study approach cross-sectional. This study was conducted in November 2014 as many as 210 students Junior High School in Pekanbaru which has been designated by the Department of Education the city of Pekanbaru. The results showed that a good social families as many as 206 respondents (98.10%), social support good school as much as 210 respondents (100%) and social support good peers as 204 respondents (97.14%).Keywords: social support, attitudes smoking, adolescents